A Shiva lingam made in black stone with a Nandi figure - Temples of India Project Team (Jio Institute, 2024)
A small shrine, possibly a newer construction, is placed off-centred to the right facing the garbhagriha. Further steps lead to the third level, on a projected platform. The subsidiary shrine has arched openings on the west, (seen here) east and north sides with a rectangular entrance inside an arched niche on the south side. A Shiva lingam made in black stone is installed inside with a Nandi figure next to it. An earthen pot is installed on a tripod which drips water over the Shiva lingam.